Implementasi ITIL V3 dan COBIT 5 Dalam Manajemen Masalah TI di CV. Warajaya Solve Techindo - Brian Firmansyah Kartono Soebari; Siti Mukaromah; Asif Faroqi (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Information technology continues to evolve over time, and this development can be leveraged across various organizational sectors. CV. Warajaya Solve Techindo, an IT Solution company, relies heavily on the implementation of information technology to support its business processes. With numerous IT services sold and used by WaySolve, new risks or problems are bound to arise. Unfortunately, WaySolve currently lacks clear guidelines for problem management. The aim of this thesis is to create SOP related to problem management that CV. Warajaya Solve Techindo can use as a reference or standard for resolving IT issues. The SOP is developed using the ITIL V3 and COBIT 5 frameworks, as both provide activities relevant to the problem management process based on existing guidelines.This thesis involves several stages: Data Collection and Analysis, SOP Document Preparation, and SOP Document Adjustment. The outcome of this thesis includes two standard operating procedure documents for IT problem management, as well as two forms with six actors assigned roles in each activity.